Annotated checklist of the moths and butterflies (Lepidoptera) of Canada and Alaska - Jeremy R. deWaard (Pensoft Publishers, 2018)
The first comprehensive checklist of the Lepidoptera of Canada and Alaska is presented. Taxonomic papers, historical regional checklists, and many collections were consulted to prepare the list. The known distributions of species are listed for the provinces and territories of Canada and the state of Alaska in the USA. The province of Newfoundland and Labrador is further divided into separate listings. A total of 5431 species belonging to 82 families are confirmed as occurring in Canada and Alaska, as well as 53 species that have been reported from the region but not yet verified, 19 species listed as interceptions or unsuccessful introductions, and 52 species listed as probably occurring in the region. A total of 318 species have been reported in error in historical works, and they are listed as well, clearly indicated as erroneous records. All erroneous records and uncertain listings are detailed with notes. All Nearctic subspecies and synonyms are included in the list, except for butterfly subspecies (and their synonyms) that do not occur in the region.